Tidy up - The unfolded protein response in sepsis - Vivas, Wolfgang; Weis, Sebastian (Frontiers in Immunology, 2022)
Pathogens, their toxic byproducts, and the subsequent immune reaction exert different forms of stress and damage to the tissue of the infected host. This stress can trigger specific transcriptional and post-transcriptional programs that have evolved to limit the pathogenesis of infectious diseases by conferring tissue damage control. If these programs fail, infectious diseases can take a severe course including organ dysfunction and damage, a phenomenon that is known as sepsis and which is associated with high mortality. One of the key adaptive mechanisms to counter infection-associated stress is the unfolded protein response (UPR), aiming to reduce endoplasmic reticulum stress and restore protein homeostasis. This is mediated via a set of diverse and complementary mechanisms, i.e. the reduction of protein translation, increase of protein folding capacity, and increase of polyubiquitination of misfolded proteins and subsequent proteasomal degradation. However, UPR is not exclusively beneficial since its enhanced or prolonged activation might lead to detrimental effects such as cell death. Thus, fine-tuning and time-restricted regulation of the UPR should diminish disease severity of infectious disease and improve the outcome of sepsis while not bearing long-term consequences. In this review, we describe the current knowledge of the UPR, its role in infectious diseases, regulation mechanisms, and further clinical implications in sepsis.